2017
DOI: 10.1038/bjc.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

Serum inflammatory markers and colorectal cancer risk and survival

Abstract: Background:Inflammation has been linked with development of some cancers. We investigated systemic inflammation in relation to colorectal cancer incidence and subsequent survival using common serum inflammatory markersDesign:A cohort of men and women aged 20 years and older in greater Stockholm area with serum C-reactive protein (CRP) and albumin measured between 1986 and 1999 were included (n=325 599). A subset of these had baseline measurements of haptoglobin and leukocytes. Multivariable Cox regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 37 publications
5
49
1
3
Order By: Relevance
“…Достоверно более высокие уровни ХС ЛПНП и низкие уровни ХС ЛПВП у пациентов основной группы по сравнению с контрольной, установленные в настоящей работе при исследовании липидного профиля сыворотки крови, согласуются с результатами работы S. Ghuman и соавт. Кроме того, у больных КРР с отдаленными метастазами выявлены достоверно более высокие уровни триглицеридов, ХС ЛПНП и соотношения ХС ЛПНП/ХС ЛПВП по сравнению с пациентами без метастазов [14].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Достоверно более высокие уровни ХС ЛПНП и низкие уровни ХС ЛПВП у пациентов основной группы по сравнению с контрольной, установленные в настоящей работе при исследовании липидного профиля сыворотки крови, согласуются с результатами работы S. Ghuman и соавт. Кроме того, у больных КРР с отдаленными метастазами выявлены достоверно более высокие уровни триглицеридов, ХС ЛПНП и соотношения ХС ЛПНП/ХС ЛПВП по сравнению с пациентами без метастазов [14].…”
Section: Discussionunclassified
“…Если для α-линоленовой (октадекатриеновой) Таблица 3. Содержание видов жирных кислот в мембранах эритроцитов и сыворотке крови у пациентов с колоректальным раком и в группе сравнения (M ± SD), % 8,11,14,17) достоверное (p = 0,007) повышение отмечено только в сыворотке крови, хотя и в мембранах эритроцитов наблюдалась та же тенденция. Для докозатетраеновой 7,10,13,16-22:4 кислоты выявлена инверсная ситуация -уровень ее был достоверно выше в мембранах эритроцитов пациентов с КРР (p <0,0001), а в сыворотке отмечена лишь тенденция к повышению (p = 0,097).…”
Section: экспериментальные статьиunclassified
See 1 more Smart Citation
“…Results from previous studies of CRP in relation to CRC and colorectal adenoma risk, including meta-analyses, have been mixed (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Some have been suggestive of a relation between higher CRP levels and increased risk of CRC (7)(8)(9)(10)(11) and colorectal adenoma (12,13), whereas others have been inconclusive (14)(15)(16) or null (17)(18)(19). A large Mendelian randomization study of more than 30,000 CRC cases from three international consortia found no evidence of a causal relation between genetically determined inflammation reflected by CRP and CRC risk (20), while three other studies of CRP-related genetic variants suggested a relation (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have established a link between host inflammatory response and oncologic outcomes . Furthermore, cancer patients often present with elevated peripheral blood cell numbers, acute‐phase proteins and decreased total albumin levels .…”
Section: Introductionmentioning
confidence: 99%